2022
DOI: 10.1158/2643-3230.bcd-21-0181
|View full text |Cite
|
Sign up to set email alerts
|

Blockade or Deletion of IFNγ Reduces Macrophage Activation without Compromising CAR T-cell Function in Hematologic Malignancies

Abstract: Massachusetts General Hospital (MGH). M.V.M. is an inventor on additional patents related to adoptive cell therapies held by MGH and University of Pennsylvania (some licensed to Novartis). M.V.M. holds equity in TCR2, Century Therapeutics, 2Seventy Bio, and has served as a consultant for multiple companies involved in cell therapies. M.V.M. receives sponsored research support from KitePharma and Novartis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 44 publications
5
50
0
Order By: Relevance
“…The blockade of IFN-γ with emapalumab or the IFN-γ knock-out in CAR-T cells prevented the activation of pro-inflammatory macrophages together with the associated cytokine release. 51 , 56 , 57 While these studies did not show a negative impact on the efficacy of IFN-γ KO CAR-T cells, other studies showed that IFN-γ blockade decreased the accumulation of CD8 + T cells within tumors after treatment with an anti-HER2xCD3 TDB. In particular, the blockade of IFN-γ prevented the release of essential chemokines involved in T cell recruitment.…”
Section: Cytokine Targeted Approachesmentioning
confidence: 88%
“…The blockade of IFN-γ with emapalumab or the IFN-γ knock-out in CAR-T cells prevented the activation of pro-inflammatory macrophages together with the associated cytokine release. 51 , 56 , 57 While these studies did not show a negative impact on the efficacy of IFN-γ KO CAR-T cells, other studies showed that IFN-γ blockade decreased the accumulation of CD8 + T cells within tumors after treatment with an anti-HER2xCD3 TDB. In particular, the blockade of IFN-γ prevented the release of essential chemokines involved in T cell recruitment.…”
Section: Cytokine Targeted Approachesmentioning
confidence: 88%
“…The IL-6, IL-10, and IFN-γcytokines are the strongest contributors to CRS development, and IL-6 is a core cytokine in CRS pathophysiology ( 106 , 108-110 ). Cytokine responses generated by CAR-T and bystander macrophage activation can lead to Macrophage Activation Syndrome that contributes to therapy-derived immunotoxicity ( 111 ). A murine xenogeneic model of ALL with human 1928z CAR-T cell infusion was used to interrogate the role of different cell types in the production of inflammatory cytokines such as IL6 and IL1β that drive acute CRS identified macrophages as the main contributors to the pathogenesis of CRS ( 112 ).…”
Section: Biomarkers In Actmentioning
confidence: 99%
“…A murine xenogeneic model of ALL with human 1928z CAR-T cell infusion was used to interrogate the role of different cell types in the production of inflammatory cytokines such as IL6 and IL1β that drive acute CRS identified macrophages as the main contributors to the pathogenesis of CRS ( 112 ). In this line, INF-γ produced on CAR-T cell activation has been shown to activate macrophages triggering a CRS-like cytokine release, and IFN blockade abolished macrophage-mediated cytokine production, diminishing cytokine-derived toxicities, increasing CAR-T persistence, and improving overall antitumor response ( 111 ). Fever and high monocyte chemoattractant protein 1 (MCP-1) levels within 36 hours after the infusion of CAR-T cells are considered to be predictors of severe CRS and ICANS with the best sensitivity and specificity ( 113 ).…”
Section: Biomarkers In Actmentioning
confidence: 99%
“…CAR T cells as effectors, NALM-6 tumor cells as targets, and pre-functionalized beads coated with IFN-γ capture antibody as cytokine sensors, were loaded sequentially onto a nanowell grid array, and the kinetics of killing and end-point cytokine secretion from the same cells was monitored using TIMING (Figure 1A-B, Supplementary Video 1). We chose to track IFN-γ because of the known impact of CAR T cell derived IFN-γ in shaping the susceptibility of tumors, enabling endogenous host immunity, and the potential for toxicity (17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%